KERJASAMA KEANTARIKSAAN INDONESIA-INDIA DALAM PENGEMBANGAN TEKNOLOGI ANTARIKSA PERIODE 2017-2020 - Nurannisa Nadya Firdaus (2021)
In this civilization, from the beginning of history until about a century ago, mankind had only two physical domains in which to operate, land and sea. Then in the mid-20th century, precisely during the Cold War, space emerged as a new domain of strategic value. It is not only developed countries that make space a matter of interest and concern, but also developing countries. Many developing countries do not have adequate resources and capabilities to develop their space technology independently, one of them is Indonesia. To realize its interests in the field of space, Indonesia has made various efforts, one of which is by establishing cooperation. Indonesia has established bilateral and multilateral cooperation with several countries, one of which is India. The main focus of this study is to describe the bilateral cooperation carried out by Indonesia and India in the field of space. The research method used in this research is a qualitative case study with a descriptive type of research. Bilateral cooperation, national interests, and space power are used to analyze the implementation of this space cooperation. With the method and framework of thought, the results of this study are that there are no concrete results yet from the implementation of Indonesia-India space cooperation in 2017-2020 to the development of Indonesia's space technology.